Association between poor oral health and deterioration of appetite in older age: results from longitudinal analyses of two prospective cohorts from the UK and USA - Sheena E Ramsay; Olia Papacosta; S Goya Wannamethee; John C Mathers; Peter H Whincup; Lucy Lennon; Ziyi Cai; Suruchi G Ganbavale; Robert Weyant (BMJ Open)
Objective This study investigated the association of poor oral health with appetite loss and deterioration in appetite longitudinally in older adults.Design Cross-sectional and longitudinal observational study.Setting Data came from two population-based cohorts of older adults from the UK and USA.Participants The British Regional Heart Study (BRHS) included men (n=1348, age=79–87 years in 2016–2017 at baseline and 81–89 years in 2018–2019 at follow-up). The US Health, Aging and Body Composition (HABC) Study included men and women (n=2998, age=71–77 years in 1998–1999 at baseline and 73–79 years in 2000–2001 at follow-up). Objective and self-reported oral health measures were collected.Outcome measures Loss of appetite, at baseline and 2-year follow-up, was based on the Simplified Nutrition Assessment Questionnaire in the BRHS and self-reported appetite loss in the HABC Study. In the BRHS, changes in oral health over time were also assessed. Logistic regression models were adjusted for sociodemographic, behavioural and health-related factors.Results Cross-sectionally, poor self-rated oral health, dry mouth, eating or chewing difficulty, food avoidance and cumulative oral health problems were associated with appetite loss in both studies. Longitudinally, in the BRHS, dry mouth (OR=2.12 (95% CI=1.40 to 3.20)), eating or chewing difficulty (OR=1.59 (95% CI=1.02 to 2.48)), food avoidance (OR=1.75 (95% CI=1.16 to 2.65)) and cumulative oral health problems (OR=2.84 (95% CI=1.80 to 4.50)) at baseline were associated with sustained poor/deterioration in appetite over the follow-up, after full adjustment. In the HABC Study, self-rated oral health ((OR=1.13 (95% CI=1.01 to 1.27)), tooth loss (OR=1.78 (95% CI=1.15 to 2.76)), dry mouth (OR=1.76 (95% CI=1.02 to 3.03)), eating or chewing difficulty (OR=1.88 (95% CI=1.41 to 2.50)) and cumulative oral health problems (OR=1.89 (95% CI=1.33 to 2.70)) at baseline were associated with sustained poor/deterioration in appetite during follow-up. In the BRHS, sustained poor/deterioration in oral health markers (self-rated oral health, dry mouth, eating or chewing difficulty, food avoidance, loose denture/s) over the follow-up were associated with sustained poor/deterioration of appetite.Conclusion Oral health is a potentially important contributor to maintaining good appetite in older age.